On the numerical solution for nonlinear elliptic equations with variable weight coefficients in an integral boundary conditions - Čiupaila, Regimantas; Pupalaigė, Kristina; Sapagovas, Mifodijus (Nonlinear Analysis: Modelling and Control, 2021)
In the paper the two-dimensional elliptic equation with integral boundary conditions is solved by finite difference method. The main aim of the paper is to investigate the conditions for the convergence of the iterative methods for the solution of system of nonlinear difference equations. With this purpose, we investigated the structure of the spectrum of the difference eigenvalue problem. Some sufficient conditions are proposed such that the real parts of all eigenvalues of the corresponding difference eigenvalue problem are positive. The proof of convergence of iterative method is based on the properties of the M-matrices not requiring the symmetry or diagonal dominance of the matrices. The theoretical statements are supported by the results of the numerical experiment.